0
$\begingroup$

$\int_{V}\partial_{j} T_{ij}dV = \int_{\partial V}T_{ij}dS_{j} $ is the divergence theorem for a second rank tensor. I need to show that this is true.I tried to mimic the proof for "the normal" divergence theorem but couldn't succed:

$\int_{V}\vec{∇}\cdot \vec{F}dV =\int_{\partial V}\vec{F}\cdot d\vec{S}$,

$V=[(x,y,z)|(x,y) \in D, f(x,y)<z<g(x,y)]$,

$\int_{V}(\partial_{x} F_{x}+\partial_{y} F_{y}+\partial_{z} F_{z})dxdydz$ this is where it stopps. How does one interpet this to a second rank tensor?

Does any one know a way to tackle this problem? Thank you for answers.

$\endgroup$
1
$\begingroup$

First note that $\int_\Omega \vec{\nabla} \cdot \vec{F} \, dV = \oint_{\partial \Omega} \vec{F} \cdot d\vec{S}$ can be written as $\int_\Omega \partial_i F_i \, dV = \oint_{\partial\Omega} F_i dS_i.$

Now let $\vec A = (A_i)$ be a constant vector field. Then $$ A_i \int_\Omega \partial_{j} T_{ij} \, dV = \int_\Omega \partial_j (A_i T_{ij}) \, dV = \oint_{\partial \Omega} A_i T_{ij} \, dS_j = A_i \oint_{\partial \Omega} T_{ij} \, dS_j. $$ This is valid for all constant $\vec A,$ e.g. for $\vec A = e_1, e_2, e_3$ which gives that $$\int_\Omega \partial_j T_{ij} \, dV = \oint_{\partial\Omega} T_{ij} \, dS_j$$ for $i=1,2,3,$ i.e. the formula is valid for all $i.$

$\endgroup$
  • $\begingroup$ Thank you for answer, but I don't really understand the argument. How come you make them $\int_\Omega \partial_j (A_i T_{ij}) \, dV = \oint_{\partial \Omega} A_i T_{ij} \, dS_j$ in the first place, and why would it matter if it is valid for all constant vectors? $\endgroup$ – 123 Jul 19 '18 at 20:04
  • 1
    $\begingroup$ That equality is just $\int_\Omega \vec{\nabla} \cdot \vec{F} \, dV = \oint_{\partial \Omega} \vec{F} \cdot d\vec{S}$ for $F_j = A_i T_{ij},$ and you know from before that this is true. $\endgroup$ – md2perpe Jul 19 '18 at 20:29
  • 1
    $\begingroup$ If $A_i u_i = A_i v_i$ for all constant $A_i$ then $u_i = v_i$ (for all $i$). This is because you can take $\vec A = e_j,$ the unit vector field in the $j$th coordinate direction. But since $A_i = (e_j)_i = \delta_{ij}$ (Kronecker delta), you then get $u_j = v_j$ for that $j$. But since you can to that for any $j$ you get $u_j = v_j$ for all $j$. $\endgroup$ – md2perpe Jul 19 '18 at 20:36
  • 1
    $\begingroup$ Yes, the product $A_i T_{ij}$ is a rank 1 tensor on which we can apply our already known theorem/formula. $\endgroup$ – md2perpe Jul 19 '18 at 20:49
  • 1
    $\begingroup$ Very informally you might say so, but if you want to be mathematically strict you should not use that wording. $\endgroup$ – md2perpe Jul 19 '18 at 20:59

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.